Causes of delay on highway construction project in Klang valley - Karunakaran S.; Ramli M.Z.; Malek M.A.; Musir A.A.; Imran N.F.; Fuad N.F.S.M.; Zawawi M.H.; Zainal M.Z. (American Institute of Physics Inc., 2023)
Construction is a vital industry in all of the countries especially in the developing country such as Malaysia. Moreover, highway construction is very important as it act as a network to connect from one place to another. Delay is a major problem in the construction industry and it is quite challenging to avoid in the construction project. When the project delays, it definitely affects the cost and the quality of the project as well. The main objective of this study is to determine the factors that contributes to the delays in the highway construction project and its significance level towards the respective project. Data collection are gathered based on pilot survey and questionnaire. Then, it followed with the ranking and significance level analysis with the method of Relative Importance Index. Thus, based on the RII ranking, the top five factors was the improper planning, weather, poor site management, poor site investigation and underground utilities. The RII value for the top most and lowest factor was 0.851 and 0.671 respectively. 2018 Author(s).